Expression of matrix metalloproteinases in cerebral amyloid angiopathy-a systematic review - Gu, Hanying; Shi, Xiuxia; Zhang, Jiangtao (Frontiers in Neurology, 2026)
ObjectiveThis study aimed to conduct a systematic review of the expression levels of matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs) in cerebral amyloid angiopathy (CAA).MethodsThis systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The PubMed, Embase, and Web of Science databases were searched to identify relevant studies. Two researchers independently screened the literature, extracted data, and assessed the study quality.ResultsFive studies evaluating a total of 442 participants were included. The findings revealed dysregulation of the MMP/TIMP system in the cerebral blood vessels of patients with CAA. Specifically, in comparison with patients without CAA, those with CAA showed significantly upregulated expression of TIMP-3 and TIMP-4 in the cerebral blood vessels, and TIMP-4 levels were positively correlated with the severity of CAA. MMP-9 expression in patients with CAA-related intracerebral hemorrhage (CAA-ICH) was significantly higher than in those without hemorrhage, while TIMP-3 expression was lower in patients with CAA-ICH; these findings suggest that an imbalance between MMP-9 and TIMP-3 may increase the risk of hemorrhage. Cerebrospinal fluid (CSF) and serum biomarker studies showed that patients with CAA had decreased TIMP-4 levels in the CSF and significantly lower serum MMP-2 levels.ConclusionThe findings of this study indicated an imbalance in the MMP/TIMP system in CAA, which may be involved in its vascular pathological mechanism. However, the existing evidence is insufficient to support the use of MMPs/TIMPs as reliable biomarkers for CAA. Therefore, further evaluation of their diagnostic and therapeutic value is required in future studies.Systematic review registrationThis systematic review was registered in PROSPERO (Unique Identifier: CRD420251230405). The protocol can be accessed at: https://www.crd.york.ac.uk/PROSPERO/view/CRD420251230405, CRD420251230405.